Perkembangan Ilmu Hukum Tata Negara Dalam Perspektif Demokrasi dan Rule of Law di Indonesia - Sari Gustriani, Wulan; Aswata, I Gede Pantja; Arifin, Firdaus; Noval , Sayid Mohammad Rifqi (Green Publisher Indonesia, 2025)
This study examines the development of Constitutional Law in Indonesia from the perspective of democracy and the rule of law using a normative legal research method. The evolution of Indonesia’s constitutional system since independence reveals close ties with the dynamics of democracy, ranging from the early parliamentary system, guided democracy, and the authoritarian New Order, to the constitutional reforms that strengthened checks and balances. The application of the rule of law affirms the constitution as the highest norm and a substantive instrument of democracy, although in practice it still faces challenges such as weak law enforcement, political intervention, and a lack of legal culture. The findings confirm that Constitutional Law in Indonesia is never static but continually evolves according to political configurations, social dynamics, and historical needs. The study highlights the importance of consistently strengthening the rule of law to ensure constitutional law functions effectively in safeguarding justice, human rights, and democratic resilience in Indonesia.